Robust control of 3-DOF parallel robot driven by PMAs based on nominal stiffness model. (19th May 2017) - Liu, Kai; Xu, Jiaqi; Ge, Zhishang; Wang, Yangwei; Zhao, Dongbiao; Lu, Yonghua
Abstract: This paper deals with an efficient implementation of robust controller on 3-DOF parallel robot driven by pneumatic muscle actuators (PMAs). PMA is a new flexible pneumatic actuator with relatively complex mathematical model. For the purpose of controlling robot, a new method to establish mathematical model of PMA is proposed. Based on analysis of stiffness characteristics of PMA, the concept of nominal stiffness coefficient is put forward and applied to establishment of mathematical model of PMA. According to 3-DOF robotic decoupling property, two rotational freedom of X, Y -axis are controlled by robust controller. Based on the dynamics, trajectory tracking control in simulation performs well under the circumstances of different interference via robust controller. Experimental results show that robust controller has satisfactory tracking performance and the characteristic of high real time. Its maximum tracking errors around X – Y axis are not more than 0.4°. Due to its less interference in motion around Z -axis, controlling Z -axis also has good tracking performance via computed torque method. Abstract :